ENVIRONMENTAL CHANGES DURING THE LATE MIOCENE TO PLEISTOCENE USING SMALL FORAMINIFERA AND PALYNOMORPHS IN THE KUTAI BASIN, EAST KALIMANTAN - Nisa, Firda Aulya; Jurnaliah, Lia; Winantris, Winantris; Nugrahanto, Kuntadi (Marine Geological Institute of Indonesia, 2024)
The Kutai Basin is one of the large basins in East Kalimantan which was formed during the Tertiary Period. The sedimentation process in this basin is strongly influenced by sea level changes. This study conducts quantitative analysis using the abundance of small foraminifera and palynomorphs in well “FN O-1” located in the northern part of offshore Kutai Basin. It applies the Planktonic-Benthic Ratio to determine the range of the bathymetric-related environments in the entire depth interval. The aims of this study are to interpret the sequence stratigraphy in the Kutai Basin using small foraminifera and palynomorphs associated with sea level changes. Three sequence stratigraphy phases are identified; TST (Transgressive System Tract), HST (Highstand System Tract), and FSST (Falling Stage System Tract), from the Late Miocene to Pleistocene in an inner to outer neritic environment. The results of the P/B ratio calculation show that wells with a depth of 1,230 feet to 12,180 feet are predominantly located in the inner neritic zone with a ratio percentage less than 20%. The highest abundance of small benthic foraminifera reaching 534 individuals was found at a depth of 1,650 feet within the TST phase. The most abundant planktonic foraminifera (452 individuals) was observed at a depth of 1,350 feet during the TST-HST transition. The FSST revealed the most abundance of mangrove palynomorphs with 100 fossil grains at 11,640 feet and 56 back-mangrove palynomorphs fossils were identified within the TST at 2,340 feet. This study concludes that the abundance of small foraminifera and palynomorphs suggests both marine and terrestrial influences on the basin.